Communication strategy to improve women's political participation in Indonesia - Uspal Jandevi (Association for Scientific Computing Electrical and Engineering (ASCEE), 2019)
This paper aims to determine how the communication strategy used to improve women's political participation in Indonesia. The essence of the communication strategy is planning and management to achieve one goal. To reach this goal, strategy functioned not only as a roadmap to lead the way but also has to show how the operational tactics. Communication strategy is a blend of communication planning and communication management to attain a specific purpose. To compose communication strategy, there are several factors which have to be considered necessary. First, knowing the public is the first step fora communicator to create effective communication. Note that in the communication process, the audience is active instead of passive. So between the communicator and communicant not only occurs relations but also influence that affect each other. Second, compile message, namely determining theme and subject. The main requirement to change public from this message is the capability to arouse their concern. The concern is a central observation. Thus not all who observed could trigger attention. Therefore the beginning of communication effectivity is the rise of the public’s attention toward the delivered messages.